Stroke - Caplan, Louis R. (Oxford : Oxford University Press, 2011)
The last decade has seen major advances in diagnostic technology available to clinicians and development of a larger therapeutic armamentarium. These rapid changes have made it difficult for non-stroke specialists to keep up.'Stroke' covers common and important topics in the diagnosis and treatment of stroke.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cerebrovascular disease -- Case studies